Historical chemical annotations of Cinchona bark collections are comparable to results from current day high-pressure liquid chromatography technologies. (1st March 2020) - Canales, Nataly Allasi; Gress Hansen, Tobias Nikolaj; Cornett, Claus; Walker, Kim; Driver, Felix; Antonelli, Alexandre; Maldonado, Carla; Nesbitt, Mark; Barnes, Christopher J.; Rønsted, Nina
Abstract: Ethnopharmacological relevance: Species of the genus Cinchona (Rubiaceae) have been used in traditional medicine, and as a source for quinine since its discovery as an effective medicine against malaria in the 17th century. Despite being the sole cure of malaria for almost 350 years, little is known about the chemical diversity between and within species of the antimalarial alkaloids found in the bark. Extensive historical Cinchona bark collections housed at the Royal Botanic Gardens, Kew, UK, and in other museums may shed new light on the alkaloid chemistry of the Cinchona genus and the history of the quest for the most effective Cinchona barks. Aim of the study: We used High-Pressure Liquid Chromatography (HPLC) coupled with fluorescence detection (FLD) to reanalyze a set of Cinchona barks originally annotated for the four major quinine alkaloids by John Eliot Howard and others more than 150 years ago. Materials and methods: We performed an archival search on the Cinchona bark collections in the Economic Botany Collection housed in Kew, focusing on those with historical alkaloid content information. Then, we performed HPLC analysis of the bark samples to separate and quantify the four major quinine alkaloids and the total alkaloid content using fluorescence detection. Correlations between historic and current annotations were calculated using Spearman's rank correlation coefficient, before paired comparisons were performed using Wilcox rank sum tests. The effects of source were explored using generalized linear modelling (GLM), before the significance of each parameter in predicting alkaloid concentrations were assessed using chi-square tests as likelihood ratio testing (LRT) models. Results: The total alkaloid content estimation obtained by our HPLC analysis was comparatively similar to the historical chemical annotations made by Howard. Additionally, the quantity of two of the major alkaloids, quinine and cinchonine, and the total content of the four alkaloids obtained were significantly similar between the historical and current day analysis using linear regression. Conclusions: This study demonstrates that the historical chemical analysis by Howard and current day HPLC alkaloid content estimations are comparable. Current day HPLC analysis thus provide a realistic estimate of the alkaloid contents in the historical bark samples at the time of sampling more than 150 years ago. Museum collections provide a powerful but underused source of material for understanding early use and collecting history as well as for comparative analyses with current day samples. Graphical abstract: Image 1